PERAN TEKNOLOGI KOMUNIKASI DALAM MENINGKATKAN EFEKTIVITAS PEMASARAN DIGITAL PADA GENERASI Z - Engelbert, Sheron Mariana Alezandra (Universitas 17 Agustus 1945 Surabaya, 2025)
The transformation of communication technology has significantly altered digital marketing strategies, particularly in targeting Generation Z, known as